Nutritional Assessment and Comparison between Brown and Milled Rice Landraces (Anadi, Bhotange, and Kalo Nuniya) of Nepal (Tribhuvan University Journal of Food Science and Technology, 2023)
The main objective of this study was to assess and compare the nutritional quality of brown- and milled rice landraces (Kalo Nuniya, Anadi, and Bhotange) of Koshi Province. Paddy samples were cleaned to remove dockage and sun-dried until about 13-14% moisture to ensure maximum hulling- and milling recovery. Paddy samples were shelled and milled to obtain brown (unpolished) rice and milled (white or polished) rice, respectively and were stored in double-sealed re-closable low-density polyethylene (LDPE) zipper bags (62.5 µm) at ambient temperature (23-27°C) until analysis. As expected, brown rices had better nutritional profiles than their milled counterparts with significantly higher (p